El potencial maderero y la ecología de los bosques amazónicos del Perú - Takahashi, Luis (2015)
Peru’s Amazon rainforest is being destroyed because the timber industry only uses 3% of trees per hectare. Therefore, timber companies cannot be established in the forest, and 97% of trees are unused. These trees are eventually burned to clear land for formal and informal agriculture. This article proposes to use more trees given that records of the last 40 years show that all tree species can be used for some purpose if they are processed appropriately with simple sawmill and drying techniques. The analysis shows that if less than 7% of the available trees is used, it will be ﬁnancially and economically feasible to establish primary industries in the forest itself. This creates permanent job positions and enables a sustainable use and renovation of the forest; thus ensuring the preservation of the Amazon rainforest, which does not allow growing any foreign tree species.